The Effect of Competence and Compensation on The Performance of Family Support Teams in Stunting Prevention Programs with Motivation as an Intervening Variable in Kabupaten Garut - Nurnafajrin, Riska; Kania, Ikeu; Ulumudin, Aceng; Geusan Akbar, Gugun; Mulyaningsih (Ann Publisher, 2025)
Background. Stunting remains a serious issue in Kabupaten Garut despite various intervention efforts. Aims. This study analyzes the effect of competence and compensation on the performance of the Tim Pendamping Keluarga (TPK), with motivation as an intervening variable. Methods. The research employs Partial Least Squares-Structural Equation Modeling (PLS-SEM) with 375 respondents selected using the Slovin technique. The Importance Performance Map Analysis (IPMA) approach was used to identify variables that greatly impact performance but need improvement. Result. The study results show that competence significantly affects motivation, with a path coefficient of 0.549 and an f-square of 0.506 (high). Compensation also significantly positively affects motivation, with a path coefficient of 0.288 and an f-square of 0.139 (moderate). Motivation significantly affects performance, with a path coefficient of 0.367 and an f-square of 0.311 (high). Competence significantly influences performance, with a path coefficient of 0.503 and an f-square of 0.649 (high), while compensation moderately affects performance, with a path coefficient of 0.153 and an f-square of 0.079. Upsilon (υ) indicates that motivation mediates the relationship between competence and performance, with an Upsilon (υ) value of 0.076 (moderate), while for compensation and performance, the Upsilon (υ) value is 0.002 (low). Conclusion. IPMA identifies that motivation has the highest impact on performance, followed by competence and compensation. Recommendation. Recommendations include enhancing competence through technology training and implementing fairer compensation policies to improve motivation and performance in TPK for accelerating stunting reduction efforts.